Penyusunan TOR Tugas Besar Studio Perancangan Arsitektur Bangunan Sederhana Prodi Arsitektur Bangunan Gedung Politeknik Negeri Pontianak - Fiska Hidayat (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
TOR, short for Terms of Reference, is a guide that explains in detail what must be achieved in a project, including aims, scope of works, methodological approach, and success criteria for evaluation. This research aims to develop a guide for preparing an effective and appropriate TOR for the Large Task of the Simple Building Architecture Design Studio for the Building Architecture Study Program at the Politeknik Negeri Pontianak. The Simple Building Architectural Design Studio course is a new course combining Architectural Design, Form Aesthetics and Technical Drawing courses. The emergence of new classes due to changes in the curriculum, is because to become someone with the profession of Architect, one of the requirements is that during the lecture period, one must have many studio classes. This research uses a descriptive qualitative approach, carried out by collecting data through interviews with stakeholders, field observations and document collection. The research results show that the TOR is more adaptive to the Simple Building Architecture Design Studio course condition. With the TOR, the tasks will be directed by the desire goals, and errors or deviations during the activity stage will be minimized.